Seduction of a proper gentleman - Alexander, Victoria (Avon romance., 2008)
Desperate to break a centuries-old curse, Lady Kathleen MacDavid heads for London, determined to brave scandal and ruin to seduce--and wed--the Earl of Norcroft.